2003
DOI: 10.3162/036298003x200944
|View full text |Cite
|
Sign up to set email alerts
|

What Happens When House Members “Run with Congress”? The Electoral Consequences of Institutional Loyalty

Abstract: This article characterizes the electoral consequences of messages of institutional loyalty and disloyalty sent by incumbent House members to their constituents. We show that, for the contemporary House, there is variation in these messages—not all incumbents in the contemporary House “run for Congress by running against Congress.” Moreover, we show that these messages can, under the right conditions, have significant electoral consequences, even after controlling for party affiliation and district political fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In many political scenarios, aspiring politicians may feel pressures to demonstrate their political independence and adopt the title of “maverick,” particularly when ratings of the parties and Congress drop as they have in recent years (Abramowitz ; Lipinski, Bianco, and Work ; Pew Research Center for the People and the Press ). This strategy is fraught with difficulties, as people affiliate with a party based on their understanding that the party represents their values and positions, so a candidate who diverges from the party platform may face punishment from voters concerned that a candidate no longer represents them (Lavine and Gschwend ; Redlawsk, Civettini, and Lau ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many political scenarios, aspiring politicians may feel pressures to demonstrate their political independence and adopt the title of “maverick,” particularly when ratings of the parties and Congress drop as they have in recent years (Abramowitz ; Lipinski, Bianco, and Work ; Pew Research Center for the People and the Press ). This strategy is fraught with difficulties, as people affiliate with a party based on their understanding that the party represents their values and positions, so a candidate who diverges from the party platform may face punishment from voters concerned that a candidate no longer represents them (Lavine and Gschwend ; Redlawsk, Civettini, and Lau ).…”
Section: Discussionmentioning
confidence: 99%
“…While this article found limited evidence that either gender or party affiliation consistently conditioned the relationship between issue disagreement and candidate's gender, the small sample size precludes firm conclusions on this point. Another next step is to test whether the issue disagreement damaging among party supporters is offset by gains among independents or members of the opposing party (see Herrnson and Curry ; Lipinski, Bianco, and Work ). This article provides a starting point for these explorations of the effects of going maverick, which are beyond the scope of the current project.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of individual voter behavior find that in numerous recent elections Americans do seem to have based their House votes, in part, on their evaluation of overall congressional job performance (Hibbing and Tiritilli 2000; Jones and McDermott 2004; McDermott and Jones 2003). Other research has shown that with an unpopular Congress in 1994, members who publicly promoted the institution suffered aggregate vote loss (Lipinski, Bianco, and Work 2003). To date, however, there has been no longitudinal empirical analysis of how congressional performance evaluations affect individual members' reelection outcomes, and no analysis of the effect that changes in partisan polarization over time have on this relationship.…”
mentioning
confidence: 99%
“…While the challenges for candidates caught in a scandal are clear, the question of whether an entire political party can "own" corruption, stained by their association with crooked incumbents is unclear. Recent scholarship on congressional elections, however, suggests the possibility, showing that the electoral margins of majority party incumbents can be reduced by poor institutional judgments, regardless of their own individual popularity (Jones 2010;Lipinski, Bianco, and Work 2003).…”
Section: "Owning" Corruptionmentioning
confidence: 96%